2013
DOI: 10.1021/jf3053862
|View full text |Cite
|
Sign up to set email alerts
|

Optimized GC-MS Method To Simultaneously Quantify Acetylated Aldose, Ketose, and Alditol for Plant Tissues Based on Derivatization in a Methyl Sulfoxide/1-Methylimidazole System

Abstract: The isomers of monosaccharide always produce multiple chromatographic peaks as volatile derivatives during gas chromatography, which may result in the overlapping of different sugar peaks. Whereas reduction and oximation of sugar carbonyl groups for GC analysis do eliminate many isomer derivatives, the approaches create new problems. One ketose can yield two peaks by oximation, and different aldoses and ketoses can yield the same alditol upon reduction, leading to the inability to detect some important monosac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…More recently, Malagon et al and Zhang et al detected rhamnitol in human urine using GC/MS (Malagon et al, 2006) and LC/MS with HILIC (Zhang, Creek, Barrett, Blackburn, & Watson, 2012). Rhamnitol was detected in the leaves of Arabidopsis thaliana, corn grains (Zea maize), and the fruit of cucumber (Cucumis sativus) by GC/MS; however, it was not found in Fuji apples, in contrast to our results (Li et al, 2013;Tan et al, 2010). In the only study of fruits, Yun et al identified rhamnitol in Satsuma mandarin (Citrus unshiu Marcovitch) (Yun et al, 2013).…”
Section: Apple Characterisation By Targeted Analysis With Annotated Mcontrasting
confidence: 99%
“…More recently, Malagon et al and Zhang et al detected rhamnitol in human urine using GC/MS (Malagon et al, 2006) and LC/MS with HILIC (Zhang, Creek, Barrett, Blackburn, & Watson, 2012). Rhamnitol was detected in the leaves of Arabidopsis thaliana, corn grains (Zea maize), and the fruit of cucumber (Cucumis sativus) by GC/MS; however, it was not found in Fuji apples, in contrast to our results (Li et al, 2013;Tan et al, 2010). In the only study of fruits, Yun et al identified rhamnitol in Satsuma mandarin (Citrus unshiu Marcovitch) (Yun et al, 2013).…”
Section: Apple Characterisation By Targeted Analysis With Annotated Mcontrasting
confidence: 99%
“…Glucose and fructose were extracted from Arabidopsis plant leaves and quantified using a new approach as described 36 . Fifty milligrams of fully expanded rosette leaves from 3-week-old Arabidopsis plants were harvested at the end of night.…”
Section: Methodsmentioning
confidence: 99%
“…Derivatization of RA samples was done following the previously described method [26]. This method was concurrently used to generate the GC-MS chromatogram of the 22 monosaccharide, disaccharide, and alditol standard substances.…”
Section: Methodsmentioning
confidence: 99%